Literature Review: New Wave Marketing, Marketing Performance, and Memorable Tourism Experience in The Tourism Sector - Pelliyezer Karo Karo; Sulastri Sulastri; Ahmad Maulana (Journal of International Conference Proceedings, 2024)
Sector Indonesian tourism is also obliged to implement draft marketing to survive and make a real contribution to state income. The digital era, of course, produces a shift for many sectors, including its impact on the tourism sector, so the marketing concept must be able to follow changes in the behavior of tourists as consumers, which is related to experience travel. This study uses the studies' bibliography to explore the relationship between implementing new-wave marketing and performance marketing and memorable tourism experiences. A total of 108 selected articles contributing to this research were searched using Publish and Perish with the electronic databases Scopus, Semantic Scholar, and Google Scholar in the publication range from 2014 to 2023. The study results show that no special studies directly linked study topics as variables within the scope of the tourism sector and other related sectors. However, the three study topics show a relationship where applied marketing tends to be legacy marketing oriented. Apart from that, no studies link function moderation or intervention from experience travel with concept marketing and performance marketing. This finding is a contribution and angle that looks new to marketing research tourists in the future.